PENGARUH KEAHLIAN, INDEPENDENSI, KECERMATAN PROFESIONAL, DENGAN ETIKA SEBAGAI VARIABEL MODERASI TERHADAP KUALITAS AUDITOR PADA INSPEKTORAT PROVINSI BENGKULU - Febriansyah, Erwin; Rasuli, M.; Hardi, Hardi (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2013)
This research was conducted using a survey method inInspectorate Bengkulu Province. This study aims to examine theinfluence of expertise, independence, due proffesional care, withethics as a moderating variable to quality auditor in the InspectorateBengkulu province. The population in this study was 6o auditors inInspectorate Bengkulu Province. The data was collected bydistributing kuesinoner to the 6o respondents, but only 55questionnaires that can be used in this study. Type of data used isprimary data with the method of data collection using questionnaires.Method of data analysis used in this study is multiple regression(multiple regression). These results indicate that the effect on thequality auditor expertise. Ethics can moderate the influence ofexpertise on audit quality. Independence has an influence on thequality of auditors. Ethics can moderate the impact on the quality ofauditor independence. Due proffesional care has an influence on thequality of auditors. Ethics can moderate the influence of dueproffesional care to quality auditor. The coefficient of determination(R2) of 0.672 illustrates that 67.2 % influenced by the quahty auditorexpertise, independence, due proffesional care, and ethics, while 32.8% is influenced by other variables.